Pengembangan Modul Digital Berbasis Etnomatematika untuk Meningkatkan Pemahaman Matematis pada Materi Peluang - Setiyaningsih, Maulida Nur; Kumala, Fitria Zana (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
The aim of this research is to develop an ethnomathematics-based digital module that is valid and effective in improving mathematical understanding. The type of research method is Research and Development (R&D) using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The results show that the ethnomathematics-based digital module is declared valid and effective for improving mathematical understanding. The validation percentage results for material and ethnomathematics context experts were 80%, media experts 80%, teachers 90%, small group tests 71.95%, and field tests 78.80% showing valid criteria. Furthermore, the t-test for two independent samples shows that there is a difference in the average mathematical understanding of the two sample classes with a sig(2-tailed) significance value of 0.000 < 0.050. The effectiveness of the ethnomathematics-based digital module on opportunity material is shown by an increase in mathematical understanding in the experimental class, namely an average N-Gain score of 0.800 in the “High” category, higher than the control class with an average N-Gain score of 0.310 in the “Medium” category. Therefore, the conclusion obtained is that the ethnomathematics-based digital module on opportunity material is effective in improving mathematical understanding.